Historical Dictionary of Costa Rica - Díaz Arias, David 1977- (Historical Dictionaries of the Americas, 2019)
Historical Dictionary of Costa Rica contains a chronology, an introduction, appendixes, and an extensive bibliography. The dictionary section has over 1,000 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture